Reconstructing ionospheric TEC over South Africa using signals from a regional GPS network - Opperman, B D L (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2008)
Radio signals transmitted by GPS satellites orbiting the Earth are modulated as they propagate through the electrically charged plasmasphere and ionosphere in the near-Earth space environment. Through a linear combination of GPS range and phase measurements observed on two carrier frequencies by terrestrial-based GPS receivers, the ionospheric total electron content (TEC) along oblique GPS signal paths may be quantified. Simultaneous observations of signals transmitted by multiple GPS satellites and observed from a network of South African dual frequency GPS receivers, constitute a spatially dense ionospheric measurement source over the region. A new methodology, based on an adjusted spherical harmonic (ASHA) expansion, was developed to estimate diurnal vertical TEC over the region using GPS observations over the region. The performance of the ASHA methodology to estimate diurnal TEC and satellite and receiver differential clock biases (DCBs) for a single GPS receiver was first tested with simulation data and subsequently applied to observed GPS data. The resulting diurnal TEC profiles estimated from GPS observations compared favourably to measurements from three South African ionosondes and two other GPS-based methodologies for 2006 solstice and equinox dates. The ASHA methodology was applied to calculating diurnal two-dimensional TEC maps from multiple receivers in the South African GPS network. The space physics application of the newly developed methodology was demonstrated by investigating the ionosphere's behaviour during a severe geomagnetic storm and investigating the long-term ionospheric stability in support of the proposed Square Kilometre Array (SKA) radio astronomy project. The feasibility of employing the newly developed technique in an operational near real-time system for estimating and dissimenating TEC values over Southern Africa using observations from a regional GPS receiver network, was investigated.
Keywords: Global Positioning System; Global Positioning System -- Data processing; Electrons -- South Africa; Ionosphere -- South Africa; Ionospheric radio wave propagation -- South Africa